First Report on Abortion Caused by Salmonella enterica subsp. enterica Serovar Enteritidis in Water Buffalo (Bubalus bubalis) - D'Angelo, Luisa; Paradiso, Rubina; Alfano, Domenico; Riccardi, Marita Georgia; Borriello, Giorgia; Galiero, Giorgio (Frontiers in Veterinary Science, 2022)
Salmonella enterica subsp. enterica Serovar Enteritidis is one of the major pathogens associated with enteric diseases in animals and humans. Thus, due to the importance of Salmonella spp. infections for animal production and public health, the aim of the present study was to describe the first detection of S. enteritidis in an aborted water buffalo fetus in southern Italy by characterizing the phylogroup profile and the antimicrobial susceptibility of the isolated pathogenic strains. The different clinical manifestations of salmonellosis in animals include diarrhea, abortion, pneumonia, septic arthritis, meningitis, and others, depending on the virulence of the serovars, infectious dose, and host immunity. This study reports the first case of abortion caused by Salmonella enterica subsp enterica serovar Enteritidis in water buffalo (Bubalus bubalis) in the Campania region, southern Italy. Complete necropsy was performed on the aborted water buffalo fetus under study, and samples and swabs from different organs were collected. Samples were processed by microbiological and molecular analyses to detect bacterial, viral, and protozoarian pathogens possibly responsible for abortion. Whole genome sequencing (WGS) was carried out to further characterize the isolated S. Enteritidis strain. Our findings highlight the crucial role of S. Enteritidis as a potential abortive agent in water buffalo and its presence should therefore be investigated in cases of bubaline abortion.